Light-emitting device, preparation method thereof and display device

By adding a thermoelectric material barrier layer between the light emitting layer of the light emitting device and the electronic functional layer, the problem of low luminous efficiency of the existing light emitting devices is solved, and the effect of improving luminous efficiency and extending service life is achieved.

CN119653982APending Publication Date: 2025-03-18TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311200878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The luminous efficiency of existing light emitting devices is low and needs to be improved.

Method used

A barrier layer prepared by thermoelectric material is added between the light emitting layer and the electronic functional layer of the light emitting device. Using the high conductivity and low thermal conductivity of the thermoelectric material, the Joule heat generated during the working process of the light emitting device is converted into electrical energy to avoid the damage to the light emitting device by rising temperature.

Benefits of technology

By reducing the exciton quenching effect between the light emitting layer and the electronic functional layer, the electron migration rate of the electronic functional layer is improved, thereby improving the luminous efficiency of the light emitting device and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653982A_ABST
    Figure CN119653982A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device, a preparation method thereof and a display device, and relates to the technical field of display. The light-emitting device comprises an anode, a light-emitting layer, a barrier layer, an electronic function layer and a cathode which are arranged in a stacked mode. Wherein the material of the barrier layer comprises a thermoelectric material. The barrier layer prepared from the thermoelectric material is additionally arranged between the light-emitting layer and the electronic function layer, on one hand, the barrier layer separates the electronic function layer from the light-emitting layer, the exciton quenching effect between the light-emitting layer and the electronic function layer can be reduced, and electrons entering the light-emitting layer are prevented from being migrated to the electronic function layer; on the other hand, the light-emitting layer emits photons in the exciton recombination process and also releases energy in the form of phonons, so that the temperature of the light-emitting device rises, the thermoelectric material has the characteristics of high conductivity and low thermal conductivity, Joule heat generated in the working process of the light-emitting device can be converted into electric energy, damage to the light-emitting device by temperature rise is avoided, and the light-emitting device is more energy-saving and environment-friendly. The light-emitting efficiency of the light-emitting device is improved and the service life of the light-emitting device is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a light-emitting device, a method for preparing the light-emitting device, and a display device including the light-emitting device. Background Art

[0002] Currently, the widely used light-emitting devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLED has become the mainstream technology in the field of display technology due to its excellent display performance, such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLED has the advantages of saturated color and adjustable wavelength of emitted light, and high quantum yield of photoluminescence and electroluminescence, and has become a strong competitor of OLED in recent years.

[0003] The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules and finally producing visible light.

[0004] At present, the luminous efficiency of light-emitting devices is relatively low and needs to be further improved. Summary of the invention

[0005] In view of this, the present application provides a light-emitting device, aiming to improve the problem of low light-emitting efficiency of existing light-emitting devices.

[0006] The embodiment of the present application is implemented as follows: a light-emitting device includes a stacked anode, a light-emitting layer, a blocking layer, an electronic functional layer and a cathode; wherein the material of the blocking layer includes a thermoelectric material.

[0007] Optionally, in some embodiments of the present application, the thermoelectric material comprises a carbon phase / ceramic phase composite material; and / or

[0008] The thickness of the barrier layer is 4-8 nm.

[0009] Optionally, in some embodiments of the present application, the carbon phase includes one or more of carbon and silicon carbide; and / or

[0010] The ceramic phase includes one or more of SiCON, Si3N4, Al2O3, BN, AlN, SiCN, SiCO, BCN, SiBCN, SiBCO, SiAlCN, and SiAlCO; and / or

[0011] The mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material is 5.4% to 41.8%.

[0012] Optionally, in some embodiments of the present application, the carbon phase / ceramic phase composite material includes one or more of C / SiCON, SiC / Si3N4, SiC / Al2O3; and / or

[0013] The materials of the anode and the cathode include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or

[0014] The material of the light-emitting layer includes 4,4'-bis(N-carbazole)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium], diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSe S, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs , GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS2, CuInSe2, AgInS2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZ One or more of nSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX3 and BMX3, where A is Cs+ ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n ≥ 2; and / or

[0015] The electronic functional layer includes one or more of an electron injection layer and an electron transport layer, and the materials of the electron injection layer and the electron transport layer include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds, respectively; the semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; and / or

[0016] The light-emitting device further comprises a hole functional layer, which is arranged between the anode and the light-emitting layer, and the hole functional layer comprises one or more of a hole injection layer and a hole transport layer; the materials of the hole injection layer and the hole transport layer respectively comprise 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N , N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenyleneethylene) alkenyl, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N ,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, one or more thereof.

[0017] Accordingly, an embodiment of the present application further provides a method for preparing a light-emitting device, comprising:

[0018] Providing a light-emitting device preform, wherein the light-emitting device preform comprises an anode and a light-emitting layer stacked in sequence;

[0019] Providing a thermoelectric material, and disposing the thermoelectric material on a side of the light-emitting layer away from the anode to form a blocking layer;

[0020] An electronic functional layer and a cathode are sequentially formed on a side of the barrier layer away from the light-emitting layer to obtain a light-emitting device; or

[0021] Providing a light-emitting device preform, wherein the light-emitting device preform comprises a cathode and an electronic functional layer stacked in sequence;

[0022] Providing a thermoelectric material, and disposing the thermoelectric material on a side of the electronic functional layer away from the cathode to form a barrier layer;

[0023] forming a light-emitting layer and an anode in sequence on a side of the barrier layer away from the electronic functional layer to obtain a light-emitting device;

[0024] Wherein, the thermoelectric material comprises a carbon phase / ceramic phase composite material.

[0025] Optionally, in some embodiments of the present application, the thickness of the barrier layer is 4-8 nm; and / or

[0026] The carbon phase includes one or more of carbon and silicon carbide; and / or

[0027] The ceramic phase includes one or more of SiCON, Si3N4, Al2O3, BN, AlN, SiCN, SiCO, BCN, SiBCN, SiBCO, SiAlCN, and SiAlCO; and / or

[0028] The mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material is 5.4% to 41.8%.

[0029] Optionally, in some embodiments of the present application, the thermoelectric material is prepared by electrospinning.

[0030] Optionally, in some embodiments of the present application, the method for forming a barrier layer includes: grinding the thermoelectric material, dissolving it in a third solvent, stirring and ultrasonicating to obtain a thermoelectric material suspension, and disposing the thermoelectric material suspension on a side of the electronic functional layer away from the cathode to form a barrier layer.

[0031] Optionally, in some embodiments of the present application, the third solvent includes one or more of dimethylformamide, dimethyl sulfoxide, cyclopentane, ethyl nitrate, xylene, anisole, decalin, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, limonene, hexane, octane, nonane, decane, dimethylacetamide, acetyl carbonate, N-methylpyrrolidone, tetrahydrofuran, ethyl acetate, and dichloromethane; and / or

[0032] The stirring time is 24h to 32h; and / or

[0033] The ultrasonic time is 30min to 60min; and / or

[0034] In the thermoelectric material suspension, the concentration of the thermoelectric material is 2 mg / mL to 5 mg / mL; and / or

[0035] The step of disposing the thermoelectric material suspension on the side of the electronic functional layer away from the cathode comprises: disposing the thermoelectric material suspension on the side of the electronic functional layer away from the cathode by spin coating or spray coating to form a barrier layer.

[0036] Correspondingly, an embodiment of the present application further provides a display device, which includes the above-mentioned light-emitting device, or the light-emitting device manufactured by the above-mentioned manufacturing method.

[0037] The light-emitting device provided in the present application has a barrier layer made of thermoelectric material added between the light-emitting layer and the electronic functional layer. On the one hand, the barrier layer separates the electronic functional layer from the light-emitting layer, which can reduce the exciton quenching effect between the light-emitting layer and the electronic functional layer, and prevent electrons entering the light-emitting layer from migrating to the electronic functional layer; on the other hand, in addition to emitting photons during the exciton recombination process, the light-emitting layer also releases energy in the form of phonons, causing the temperature of the light-emitting device to rise. Thermoelectric materials have the characteristics of high electrical conductivity and low thermal conductivity, and can convert the Joule heat generated during the operation of the light-emitting device into electrical energy, avoiding damage to the light-emitting device caused by temperature rise, and can increase the electron migration rate of the electronic functional layer, thereby improving the luminous efficiency of the light-emitting device and extending the service life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0039] Figure 1 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0040] Figure 2 is a flow chart of a method for preparing a light-emitting device provided in an embodiment of the present application;

[0041] Figure 3 This is a flow chart of another method for preparing a light-emitting device provided in an embodiment of the present application.

[0042] Reference numerals:

[0043] Anode 10; light emitting layer 20; blocking layer 30; electron functional layer 40; cathode 50; hole functional layer 60. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0045] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0046] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0047] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0048] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0049] In the light-emitting layer of a light-emitting device, the rate of exciton recombination is much greater than the rate of exciton generation, and the excited state lifetime of excitons is less than the time required for carrier injection. The carrier injection capability needs to be further enhanced to improve the performance of the light-emitting device. In addition, the conduction band positions of the electronic functional layer material and the light-emitting material are close, and spontaneous charge transfer is prone to occur, resulting in interface defects between the electronic functional layer and the light-emitting layer, causing the light-emitting material to be charged and interface charge capture, and electrons are easily transferred between adjacent layers, causing non-radiative exciton quenching, thereby degrading the photoelectric performance of the light-emitting device, reducing the luminous efficiency, and shortening the service life.

[0050] The technical solution of this application is as follows:

[0051] First, see Figure 1 The embodiment of the present application provides a light-emitting device, including a stacked anode 10, a light-emitting layer 20, a barrier layer 30, an electronic functional layer 40 and a cathode 50; wherein the material of the barrier layer 30 includes a thermoelectric material.

[0052] It should be noted that the thermoelectric material is a functional material that can convert thermal energy and electrical energy into each other.

[0053] The light-emitting device described in the present application has a barrier layer 30 made of thermoelectric material added between the light-emitting layer 20 and the electronic functional layer 40. On the one hand, the barrier layer 30 separates the electronic functional layer 40 from the light-emitting layer 20, which can reduce the exciton quenching effect between the light-emitting layer 20 and the electronic functional layer 40, and prevent electrons entering the light-emitting layer 20 from migrating to the electronic functional layer 40; on the other hand, in addition to emitting photons during the exciton recombination process, the light-emitting layer 20 also releases energy in the form of phonons, causing the temperature of the light-emitting device to rise. Thermoelectric materials have the characteristics of high electrical conductivity and low thermal conductivity, and can convert the Joule heat generated during the operation of the light-emitting device into electrical energy, avoiding damage to the light-emitting device caused by temperature rise, and can increase the electron migration rate of the electronic functional layer 40, thereby improving the luminous efficiency of the light-emitting device and extending the service life of the light-emitting device.

[0054] In some embodiments, the thermoelectric material includes a carbon phase / ceramic phase composite material. It is understood that in the carbon / ceramic composite material, the carbon phase can adjust the electron transmission to obtain high conductivity, and the ceramic phase can induce phonon scattering through boundary scattering to obtain low thermal conductivity, thereby reducing the interaction between the electronic functional layer 40 and the light-emitting layer 20 and improving the electron transmission capability.

[0055] In some embodiments, the carbon phase includes one or more of carbon and silicon carbide.

[0056] In some embodiments, the ceramic phase includes one or more of SiCON, Si3N4, Al2O3, BN, AlN, SiCN, SiCO, BCN, SiBCN, SiBCO, SiAlCN, and SiAlCO. By adding ceramic phase materials to carbon phase materials, the disorder of carbon phase materials can be increased and the graphite content can be reduced.

[0057] In some embodiments, the carbon phase / ceramic phase composite material is a fiber material.

[0058] In some embodiments, the mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material is 5.4% to 41.8%, for example, 5.4%, 6%, 8%, 10%, 15%, 20.6%, 25%, 30%, 32%, 35%, 38%, 40%, 41.8%, etc. Within the mass fraction range, the ceramic phase is conducive to uniform distribution in the carbon phase, and the carbon phase and the ceramic phase are uniformly distributed in the carbon phase / ceramic phase composite material.

[0059] In some embodiments, the carbon phase / ceramic phase composite material includes one or more of C / SiCON, SiC / Si3N4, and SiC / Al2O3. The carbon phase / ceramic phase composite material has a sea-island type nanostructure. This uniformly dispersed structure makes the ceramic phase not significantly increase the resistance, but can effectively improve the phonon boundary scattering, resulting in a decrease in the thermal transmission efficiency of phonons. The increase in the content of the ceramic phase does not prevent electrons from being transmitted through the carbon phase, thereby improving the electron mobility of the electron transport layer in the light-emitting device and further enhancing the transmission of electrons.

[0060] In some embodiments, the barrier layer 30 has a thickness of 4-8 nm, for example, 5 nm, 6 nm, 7 nm, etc. Within the thickness range, the barrier layer 30 can effectively promote the transmission of electrons and improve the luminous efficiency of the light-emitting device.

[0061] In some embodiments, the materials of the anode 10 and the cathode 50 include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Here, “ / ” represents a stacked structure. For example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence.

[0062] In some embodiments, the electronic functional layer 40 includes one or more of an electron injection layer and an electron transport layer.

[0063] In some embodiments, the materials of the electron injection layer and the electron transport layer include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds. The semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

[0064] In some embodiments, the light emitting device further comprises a hole functional layer 60. The hole functional layer 60 is disposed between the anode 10 and the light emitting layer 20. The hole functional layer 60 comprises one or more of a hole injection layer and a hole transport layer.

[0065] In some embodiments, the materials of the hole injection layer and the hole transport layer are respectively but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, (Carbazole-9-yl) triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino) triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl) diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2- ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)- N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. One or more thereof.

[0066] In some embodiments, the material of the light-emitting layer 20 includes one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0067] The organic light-emitting material includes one or more of CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)]), TCTX:Ir(mmpy)(4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium]), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing BN covalent bonds, HLCT (hybridized localized charge transfer excited state) materials, and Exciplex (exciplex) light-emitting materials.

[0068] The quantum dot luminescent material includes one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.

[0069] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots can be respectively selected from but not limited to one or more of the group II-VI compounds, group IV-VI compounds, group III-V compounds and group I-III-VI compounds. The II-VI group compounds include one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound includes one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2.

[0070] As an example, the core-shell structured quantum dots include one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0071] The perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2 + 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of the .

[0072] Second, see Figure 2 The present application also provides a method for preparing a light-emitting device, comprising:

[0073] S11: providing a light-emitting device preform, wherein the light-emitting device preform comprises an anode 10 and a light-emitting layer 20 which are stacked in sequence;

[0074] S12: providing a thermoelectric material, and disposing the thermoelectric material on a side of the light-emitting layer 20 away from the anode 10 to form a barrier layer 30;

[0075] S13: forming an electronic functional layer 40 and a cathode 50 in sequence on a side of the barrier layer 30 away from the light-emitting layer 20 to obtain a light-emitting device.

[0076] It can be understood that the light emitting device can also be an inverted light emitting device, see Figure 3 , the method for preparing the inverted light-emitting device comprises:

[0077] S21, providing a light-emitting device preform, wherein the light-emitting device preform comprises a cathode 50 and an electronic functional layer 40 which are stacked in sequence;

[0078] S22, providing a thermoelectric material, and disposing the thermoelectric material on a side of the electronic functional layer 40 away from the cathode 50 to form a barrier layer 30;

[0079] S23, forming a light-emitting layer 20 and an anode 10 in sequence on a side of the barrier layer 30 away from the electronic functional layer 40 to obtain a light-emitting device.

[0080] Wherein, the thermoelectric material comprises a carbon phase / ceramic phase composite material.

[0081] The preparation method of the light-emitting device provided in the present application adds a barrier layer 30 made of thermoelectric material between the light-emitting layer 20 and the electronic functional layer 40. On the one hand, the barrier layer 30 separates the electronic functional layer 40 from the light-emitting layer 20, which can reduce the exciton quenching effect between the light-emitting layer 20 and the electronic functional layer 40, and further improve the electron mobility in the light-emitting device; on the other hand, in addition to emitting photons during the exciton recombination process, the light-emitting layer 20 also releases energy in the form of phonons, causing the temperature of the light-emitting device to rise. Thermoelectric materials have the characteristics of high electrical conductivity and low thermal conductivity, and can convert the Joule heat generated during the operation of the light-emitting device into electrical energy, thereby avoiding damage to the light-emitting device due to temperature rise, improving the luminous efficiency of the light-emitting device, and extending the service life of the light-emitting device.

[0082] In the S11:

[0083] In some embodiments, the light emitting device preform further includes a hole functional layer 60, and the hole functional layer 60 is disposed between the anode 10 and the light emitting layer 20. The hole functional layer 60 includes one or more of a hole injection layer and a hole transport layer.

[0084] The materials of the anode 10 , the hole functional layer 60 , and the light emitting layer 20 are as described above and will not be described again here.

[0085] In S12:

[0086] In some embodiments, the method for preparing the thermoelectric material comprises:

[0087] S121, providing a carbon phase precursor, a ceramic phase precursor and a first solvent, and mixing them to obtain a mixed solution;

[0088] S122, electrospinning the mixed solution to obtain a thermoelectric material.

[0089] In S121:

[0090] In some embodiments, the carbon phase precursor includes one or more of polyacrylonitrile (PAN), acrylonitrile-styrene copolymer, acrylonitrile-methacrylic acid copolymer, acrylonitrile-butadiene copolymer, and polyacrylonitrile-amide copolymer.

[0091] In some embodiments, the ceramic phase precursor includes one or more of polysilazane, polysiloxane, polysiloxane, polysiloxazane, and polysilicon disulfide.

[0092] Furthermore, the polysilazane includes one or more of polyvinylsilazane, hexamethyldisilazane, perhydrosilazane, polyureasilazane, and hyperbranched allylpolysilazane.

[0093] In some embodiments, the first solvent includes one or more of dimethylformamide (DMF), dimethyl sulfoxide, cyclobutane, ethyl nitrate, xylene, anisole, decalin, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, limonene, hexane, octane, nonane, decane, dimethylacetamide, acetyl carbonate, N-methylpyrrolidone, tetrahydrofuran, ethyl acetate, and dichloromethane.

[0094] In some embodiments, the ratio of the ceramic phase precursor to the mass sum of the carbon phase precursor and the ceramic phase precursor is 12% to 65%, for example, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. Within the range of the ratio, it is beneficial to generate a thermoelectric material with uniform distribution of carbon phase and ceramic phase.

[0095] In some embodiments, the mixing comprises a first stirring.

[0096] Further, the rotation speed of the first stirring is 500rpm to 1500rpm, for example, it can be 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, etc. The time of the first stirring is 12h to 24h, for example, it can be 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, etc. In this way, under the conditions of the first stirring, it is beneficial for the carbon phase precursor and the ceramic phase precursor to fully contact and react to generate thermoelectric materials.

[0097] In some embodiments, after the first stirring, a second solvent is added to perform a second stirring.

[0098] Furthermore, the second solvent includes one or more of acetone, xylene, anisole, decalin, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, limonene, hexane, octane, nonane, decane, tetrahydrofuran, ethyl acetate, and dichloromethane.

[0099] Further, the speed of the second stirring is 500 rpm to 1500 rpm, for example, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, etc. The time of the first stirring is 2 h to 6 h, for example, 3 h, 4 h, 5 h, etc. In this way, within the speed and time range of the second stirring, it is beneficial to further promote the dissolution of the carbon phase precursor and the ceramic phase precursor.

[0100] Furthermore, the mass ratio of the carbon phase precursor and the ceramic phase precursor to the second solvent is (2-3):1, for example, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, etc. Within the mass ratio range, the carbon phase precursor and the ceramic phase precursor are facilitated to be uniformly dispersed.

[0101] In some embodiments, in the mixed solution, the mass fraction of the carbon phase precursor is 11.9% to 13.4%, for example, it can be 12%, 12.1%, 12.2%, 12.3%, 12.4%, 12.5%, 12.6%, 12.7%, 12.8%, 12.9%, 13%, 13.1%, 13.2%, 13.3%, etc.

[0102] In some embodiments, in the mixed solution, the mass fraction of the ceramic phase precursor is 5.8% to 11.9%, for example, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11.5%, etc.

[0103] In said S122:

[0104] It should be noted that electrospinning technology is a special form of electrostatic atomization of polymer fluids. The mixed solution is jet-spun in a strong electric field. Under the action of the electric field, the droplets at the needle tip change from a sphere to a cone, and extend from the tip of the cone to obtain fiber filaments, which are finally solidified into fibers to obtain the thermoelectric material.

[0105] In some embodiments, the electrospinning is performed in an electrospinning system. The electrospinning system includes a syringe, a DC power supply, and a collector.

[0106] In some embodiments, the electrospinning comprises:

[0107] The syringe is facing the collector, and the mixed solution is loaded into the needle tube. The syringe is connected to the DC power supply, and the DC power supply is turned on to make the mixed solution spray out from the opening of the syringe and fall into the collector. After drying, the thermoelectric material is obtained.

[0108] Specifically, the syringe includes a needle tube and a metal needle connected to the needle tube, the needle tip of the metal needle faces the collector, the mixed solution is loaded into the needle tube, the metal needle is connected to the DC power supply, the DC power supply is turned on, the mixed solution flows to the metal needle, is sprayed out from the needle tip of the metal needle, falls into the collector, and the thermoelectric material is obtained after drying.

[0109] Furthermore, the diameter of the needle tip of the metal needle may be 0.5 mm to 1.1 mm, for example, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, etc.

[0110] The speed at which the mixed solution is ejected from the tip of the metal needle may be 0.4 mL / h to 0.8 mL / h, for example, 0.5 mL / h, 0.6 mL / h, 0.7 mL / h, etc.

[0111] The time for the mixed solution to be ejected from the needle tip of the metal needle may be 1.5 h to 3 h, for example, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.5 h, 2.6 h, 2.8 h, etc.

[0112] The distance between the metal needle and the collector may be 25 cm to 30 cm, for example, 26 cm, 27 cm, 28 cm, 29 cm, etc.

[0113] The output voltage of the DC power supply may be 10 kV to 25 kV, for example, 12 kV, 14 kV, 15 kV, 16 kV, 18 kV, 20 kV, 22 kV, 24 kV, etc.

[0114] The diameter of the collector may be 10 cm to 20 cm, for example, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, 16 cm, 17 cm, 18 cm, 19 cm, etc.

[0115] The drying may include drying in a vacuum oven, natural drying, or heating drying.

[0116] The drying temperature may be 50° C. to 80° C., for example, 52° C., 55° C., 58° C., 60° C., 62° C., 65° C., 68° C., 70° C., 72° C., 75° C., 78° C., etc. The drying time may be 48 h to 60 h, for example, 50 h, 52 h, 54 h, 56 h, 58 h, etc.

[0117] It can be understood that the formation of the barrier layer 30 can adopt conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip-pull method, immersion method, spray coating, roll coating, casting, slit coating, strip coating, etc.

[0118] In at least one embodiment, the method for forming the barrier layer 30 is a solution process.

[0119] Specifically, after the thermoelectric material is solidified into fibers, the process includes: grinding the thermoelectric material, dissolving it in a third solvent, stirring and ultrasonicating to obtain a thermoelectric material suspension, and disposing the thermoelectric material suspension on a side of the electronic functional layer 40 away from the cathode 50 to form a barrier layer 30.

[0120] In some embodiments, the third solvent includes one or more of dimethylformamide (DMF), dimethyl sulfoxide, cyclobutane, ethyl nitrate, xylene, anisole, decalin, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, limonene, hexane, octane, nonane, decane, dimethylacetamide, acetyl carbonate, N-methylpyrrolidone, tetrahydrofuran, ethyl acetate, and dichloromethane.

[0121] In some embodiments, in the thermoelectric material suspension, the concentration of the thermoelectric material is 2 mg / mL to 5 mg / mL, for example, 3 mg / mL, 4 mg / mL, etc.

[0122] In some embodiments, the stirring time is 24 h to 32 h, for example, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 31 h, etc.

[0123] In some embodiments, the ultrasound time is 30 min to 60 min, for example, 32 min, 35 min, 38 min, 40 min, 42 min, 45 min, 48 min, 50 min, 52 min, 55 min, 58 min, etc.

[0124] In this way, under the stirring and ultrasonic conditions, it is beneficial for the thermoelectric material to be effectively dispersed in the third solvent.

[0125] In some embodiments, disposing the thermoelectric material suspension on the side of the electronic functional layer 40 away from the cathode 50 includes: disposing the thermoelectric material suspension on the side of the electronic functional layer 40 away from the cathode 50 by spin coating or spray coating to form a barrier layer 30 .

[0126] In some embodiments, the barrier layer 30 has a thickness of 4-8 nm, for example, 5 nm, 6 nm, 7 nm, etc. Within the thickness range, the barrier layer 30 can effectively promote the transmission of electrons and improve the luminous efficiency of the light-emitting device.

[0127] The thermoelectric material is as described above and will not be described again here.

[0128] The S13

[0129] The materials of the electronic functional layer 40 and the cathode 50 are as described above and will not be described again here.

[0130] In a third aspect, the present application also relates to a display device, which includes the light-emitting device.

[0131] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0132] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0133] Example 1

[0134] This device embodiment provides a quantum dot light emitting diode, and the preparation method is as follows:

[0135] Providing an ITO glass, cleaning the ITO glass with a cleaning agent to remove stains on the surface, then ultrasonically cleaning the ITO glass with deionized water, isopropyl acetone, acetone and deionized water for 20 minutes respectively, and then drying with nitrogen to obtain an ITO anode with a thickness of 110 nm;

[0136] 40 μL of TFB solution was taken with a pipette and slowly dripped on the ITO anode for spin coating at a speed of 4000 rpm for 30 seconds, followed by annealing at a temperature of 140°C for 15 minutes to obtain a 70 nm hole functional layer;

[0137] The quantum dots with CdZnSeS as the core and ZnS as the shell were dissolved in n-octane to prepare a quantum dot solution with a concentration of 15 mg / mL; 45 μL was taken with a pipette and dropped on the hole functional layer, and spin-coated at a speed of 3500 rpm for 45 seconds, followed by annealing at a temperature of 120°C for 12 minutes to obtain a 20 nm quantum dot light-emitting layer;

[0138] 1.0 g PAN powder and 0.43 g polyvinylsilazane were dissolved in 6.03 g DMF, and the mixture was stirred at 500 rpm for 12 h. Then, 0.67 g acetone was added and stirred at 500 rpm for another 2 h to obtain a mixed solution. The mixed solution was then electrospinned to obtain the thermoelectric material C / SiCON.

[0139] The thermoelectric material C / SiCON prepared by electrospinning technology was scraped off with a blade, ground using a ball mill, dissolved in DMF after grinding, stirred for 28 hours, and then ultrasonicated for 45 minutes to prepare a thermoelectric material suspension with a concentration of 2 mg / mL. The thermoelectric material suspension was spin-coated on the quantum dot light-emitting layer to prepare a 4 nm barrier layer;

[0140] A 20 mg / mL ZnO ethanol dispersion was placed on the barrier layer and spin-coated at a speed of 5000 rpm for 30 seconds, followed by annealing at a temperature of 120° C. for 10 minutes to obtain a 40 nm electron transport layer.

[0141] The device was placed in a vapor deposition chamber and a layer of metallic silver was thermally evaporated through a mask plate to obtain a 60nm cathode;

[0142] The device was heat treated at 120° C. for 15 min and packaged to obtain a quantum dot light emitting diode.

[0143] Example 2

[0144] This embodiment is basically the same as Embodiment 1, except that the preparation method of the thermoelectric material includes: dissolving 1.0 g of PAN powder and 1 g of polyvinylsilazane in 6.4 g of DMF, dissolving at a stirring speed of 500 rpm for 12 h, adding 0.67 g of acetone, and stirring at a speed of 500 rpm for another 2 h to obtain a mixed solution, and then preparing the thermoelectric material C / SiCON by using an electrospinning technology on the mixed solution.

[0145] Example 3

[0146] This embodiment is basically the same as Embodiment 1, except that the preparation method of the thermoelectric material includes: dissolving 1.0 g of PAN powder and 0.67 g of polyvinylsilazane in 6.4 g of DMF, dissolving at a stirring speed of 500 rpm for 12 hours, adding 0.67 g of acetone, and stirring at a speed of 500 rpm for another 2 hours to obtain a mixed solution, and then preparing the thermoelectric material C / SiCON by using an electrospinning technology on the mixed solution.

[0147] Example 4

[0148] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the thermoelectric material C / SiCON is replaced by SiC / Si3N4.

[0149] Example 5

[0150] This embodiment is substantially the same as Embodiment 1, except that the concentration of the thermoelectric material suspension in this embodiment is 3.5 mg / mL.

[0151] Example 6

[0152] This embodiment is substantially the same as Embodiment 1, except that the concentration of the thermoelectric material suspension in this embodiment is 5 mg / mL.

[0153] Example 7

[0154] This embodiment is substantially the same as Embodiment 1, except that the thickness of the barrier layer in this embodiment is 6 nm.

[0155] Example 8

[0156] This embodiment is substantially the same as Embodiment 1, except that the thickness of the barrier layer in this embodiment is 8 nm.

[0157] Comparative Example

[0158] This comparative example is substantially the same as Example 1, except that no barrier layer is provided in this comparative example.

[0159] The maximum external quantum efficiency, electron mobility, turn-on voltage and lifespan T95@1000nit tests were performed on the quantum dot light-emitting diodes in Examples 1 to 8 and the comparative example, and the test results were obtained and are shown in Table 1.

[0160] Among them, the maximum external quantum efficiency, electron mobility, and turn-on voltage detection methods are: measured by LabView controlling the efficiency test system built by QEPRO spectrometer, Keithley 2400, and Keithley 6485, with a driving current of 2mA;

[0161] The test method for life span T50@100nit is: using a 128-channel life span test system customized by Guangzhou New Vision Company. The system architecture is a constant voltage and constant current source to drive QLED, test the change in voltage or current, and the photodiode detector and test system test the brightness (photocurrent) change of QLED. The brightness meter test calibrates the brightness (photocurrent) of QLED to obtain the time it takes for the initial brightness of the light-emitting diode to decay to 95%, and the driving current is 2mA; T95@1000nit refers to the time it takes for the initial brightness of the device to decay to 95%, and it is converted to the aging time at 1000nit.

[0162] Table 1

[0163]

[0164] From Table 1, we can see that:

[0165] It can be seen from Examples 1 to 3 and the comparative example that within the range provided in the present application, the mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material has no significant effect on the performance of the quantum dot light-emitting diode. The higher the proportion of the ceramic phase, the better the performance of the quantum dot light-emitting diode; Examples 1 to 3 use thermoelectric materials as a barrier layer disposed between the electron transport layer and the light-emitting layer, and the maximum external quantum efficiency, electron mobility and T95@1000nit of the prepared quantum dot light-emitting diodes are much higher than those of the quantum dot light-emitting diodes in the comparative example, and the turn-on voltage is lower than that of the quantum dot light-emitting diodes in the comparative example, indicating that the setting of the barrier layer can effectively improve the luminous efficiency of the quantum dot light-emitting diode and extend its service life;

[0166] It can be seen from Example 1, Example 4 and the comparative example that when SiC / Si3N4 is used to replace C / SiCON, the maximum external quantum efficiency, electron mobility, turn-on voltage and T95@1000nit of the quantum dot light-emitting diode do not change significantly, but whether SiC / Si3N4 or C / SiCON is used as the material of the barrier layer, the maximum external quantum efficiency, electron mobility and T95@1000nit are significantly improved relative to the quantum dot light-emitting diode of the comparative example, and the turn-on voltage is reduced;

[0167] It can be seen from Example 1, Examples 5 to 6 and the comparative example that when the concentration of the thermoelectric material suspension is appropriate, the performance of the quantum dot light-emitting diode prepared as a barrier layer is better. This is because when the concentration of the thermoelectric material suspension is too low, the thermoelectric material cannot effectively play its role. When the concentration of the thermoelectric material suspension is too high, the thermoelectric material is not easy to disperse, which will affect the final effect. The maximum external quantum efficiency, electron mobility, turn-on voltage and T95@1000nit performance of the quantum dot light-emitting diodes of Examples 1 and Examples 5 to 6 are significantly better than those of the quantum dot light-emitting diodes of the comparative example;

[0168] It can be seen from Example 1, Examples 7-8 and the comparative example that when the thickness of the barrier layer prepared by the thermoelectric material is moderate, the performance of the quantum dot light-emitting diode is better. The maximum external quantum efficiency, electron mobility, turn-on voltage and T95@1000nit performance of the quantum dot light-emitting diodes of Example 1 and Examples 7-8 are significantly better than those of the quantum dot light-emitting diodes of the comparative example.

[0169] The light-emitting device and its preparation method, and the display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A light emitting device, characterized in that: It comprises a stacked anode, a light-emitting layer, a barrier layer, an electronic functional layer and a cathode; wherein the material of the barrier layer comprises a thermoelectric material.

2. The light emitting device according to claim 1, characterized in that: The thermoelectric material comprises a carbon phase / ceramic phase composite material; and / or The thickness of the barrier layer is 4-8 nm.

3. The light emitting device according to claim 2, characterized in that: The carbon phase includes one or more of carbon and silicon carbide; and / or The ceramic phase includes one or more of SiCON, Si3N4, Al2O3, BN, AlN, SiCN, SiCO, BCN, SiBCN, SiBCO, SiAlCN, and SiAlCO; and / or The mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material is 5.4% to 41.8%.

4. The light emitting device according to claim 2, characterized in that: The carbon phase / ceramic phase composite material comprises one or more of C / SiCON, SiC / Si3N4, SiC / Al2O3; and / or The materials of the anode and the cathode include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The material of the light-emitting layer includes 4,4'-bis(N-carbazole)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium], diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSe S, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs , GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS2, CuInSe2, AgInS2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZ One or more of nSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX3 and BMX3, where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n ≥ 2; and / or The electronic functional layer includes one or more of an electron injection layer and an electron transport layer, and the materials of the electron injection layer and the electron transport layer include one or more of doped or undoped semiconductor particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds, respectively; the semiconductor particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; and / or The light-emitting device further comprises a hole functional layer, which is arranged between the anode and the light-emitting layer, and the hole functional layer comprises one or more of a hole injection layer and a hole transport layer; the materials of the hole injection layer and the hole transport layer respectively comprise 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N , N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenyleneethylene) alkenyl, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N ,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, one or more thereof.

5. A method for preparing a light-emitting device, characterized in that: include: Providing a light-emitting device preform, wherein the light-emitting device preform comprises an anode and a light-emitting layer stacked in sequence; Providing a thermoelectric material, and disposing the thermoelectric material on a side of the light-emitting layer away from the anode to form a blocking layer; An electronic functional layer and a cathode are sequentially formed on a side of the barrier layer away from the light-emitting layer to obtain a light-emitting device; or Providing a light-emitting device preform, wherein the light-emitting device preform comprises a cathode and an electronic functional layer stacked in sequence; Providing a thermoelectric material, and disposing the thermoelectric material on a side of the electronic functional layer away from the cathode to form a barrier layer; forming a light-emitting layer and an anode in sequence on a side of the barrier layer away from the electronic functional layer to obtain a light-emitting device; Wherein, the thermoelectric material comprises a carbon phase / ceramic phase composite material.

6. The preparation method according to claim 5, characterized in that: The thickness of the barrier layer is 4 to 8 nm; and / or The carbon phase includes one or more of carbon and silicon carbide; and / or The ceramic phase includes one or more of SiCON, Si3N4, Al2O3, BN, AlN, SiCN, SiCO, BCN, SiBCN, SiBCO, SiAlCN, and SiAlCO; and / or The mass fraction of the ceramic phase in the carbon phase / ceramic phase composite material is 5.4% to 41.8%.

7. The preparation method according to claim 5, characterized in that: The thermoelectric material is prepared by electrostatic spinning.

8. The preparation method according to claim 7, characterized in that: The method for forming the barrier layer comprises: grinding the thermoelectric material, dissolving it in a third solvent, stirring and ultrasonicating to obtain a thermoelectric material suspension, and placing the thermoelectric material suspension on a side of the electronic functional layer away from the cathode to form a barrier layer.

9. The preparation method according to claim 8, characterized in that: The third solvent includes one or more of dimethylformamide, dimethyl sulfoxide, sulfolane, ethyl nitrate, xylene, anisole, decalin, cyclohexane, cyclohexene, methylcyclohexane, ethylcyclohexane, limonene, hexane, octane, nonane, decane, dimethylacetamide, acetyl carbonate, N-methylpyrrolidone, tetrahydrofuran, ethyl acetate, and dichloromethane; and / or The stirring time is 24h to 32h; and / or The ultrasonic time is 30min to 60min; and / or In the thermoelectric material suspension, the concentration of the thermoelectric material is 2 mg / mL to 5 mg / mL; and / or The step of disposing the thermoelectric material suspension on the side of the electronic functional layer away from the cathode comprises: disposing the thermoelectric material suspension on the side of the electronic functional layer away from the cathode by spin coating or spray coating to form a barrier layer.

10. A display device, characterized in that: A light-emitting device comprising the light-emitting device as claimed in any one of claims 1 to 4, or a light-emitting device manufactured by the manufacturing method as claimed in any one of claims 5 to 9.